Identification of Pollen and Food Sensitization Prevalence in Children with Different Atopic Phenotype Variants (Intermediate Study Results) - Julia G. Levina; Vera G. Kalugina; Leyla S. Namazova-Baranova; Elena A. Vishneva; Konstantin S. Volkov; Kamilla E. Efendieva; Anna A. Alekseeva; Elena V. Kaytukovа (Union of pediatricians of Russia, 2023)
Background. Identification of the prevalence of pollen and food allergen molecules sensitization in children (considering regional characteristics) is relevant and crucial for personalized preventive and treatment measures development. Objective. The aim of the study is - study the prevalence of pollen and food allergen sensitization in children with different atopic phenotype variants. Methods. This cross-sectional study included 80 children aged from 4 months to 17 years 8 months with symptoms of allergic rhinitis, food allergy, atopic dermatitis living in the Moscow metropolitan area. All children were sensitized to 9 extracts of domestic, pollen and food allergens via the ImmunoCAP method, and molecular allergy diagnosis was carried out via the ImmunoCAP ISAC technology (n = 79). One patient with symptoms of allergic rhinitis during spring without any manifestations of cross-reactive food allergy received an unreadable result of ImmunoCAP ISAC. Results. The most common sensitization among all patients was to the birch pollen allergen extract - 65%, herd grass - 46%, common mugwort - 32%. The following sensitization to major allergens was most often detected according to molecular diagnosis: birch pollen Bet v 1 - 67%, herd grass Phl p 1 - 33% and Phl p 4 - 24%, and even less mugwort Art v 1 - 11%. The lowest sensitization was to the allergy component Amb a 1 of ambrosia - 8% of cases. Sensitization to wormwood pollen extract was revealed 2.5 times more often than to major components of this allergen. Spring allergic rhinitis was diagnosed in 45 children, and 27 of them had cross-reactive food allergy. Children with allergic rhinitis during the spring period (both with or without complaints on cross-reactive food allergy) most commonly had sensitization to the allergens components of hazelnut Cor a 1.0401 and apple Mal d 1, and least often to the component of the celery allergen Api g 1. Conclusion. Birch pollen is the most common primary allergen in children of the Moscow metropolitan area with allergy. Patients with spring allergic rhinitis despite the presence of cross-reactive food allergy usually have sensitization to the components of hazelnut and apple allergens.